FACTORS INFLUENCING ADOLESCENT MENTAL HEALTH IN PESANTREN - Wahyi Sholehah Erdah Suswati; Zidni Nuris Yuhbaba; M.Elyas Arif Budiman (Universitas Airlangga, 2026)
Introduction: Adolescents' failure to cope with new roles and developmental tasks often leads to the emergence of mental health problems. Moreover, for adolescents who live in pesantren are required to be independent and quickly adapt because they are far from their parents and different environment from home. This study aims to analyze internal and external factors that affect the mental health of adolescents in pesantren, including autonomy and independence, coping mechanisms, spirituality, relationships with peers and social support. Method: The type of research is quantitative with a cross-sectional approach conducted on adolescent aged 13-20 years at the Pondok Pesantren Miftahul Ulum in Kalisat Jember with a total sampling technique of 49 respondents using 6 valid and reliable instruments. Data analysis used multiple linear regression tests. Results: The results showed that significant factors related to mental health were spirituality (p = 0.018), relationships with peers (p = 0.037), and social support (p = 0.042). Spirituality was the most dominant factor with an OR=3,220 value. This means that adolescents with high spirituality are 3.22 times more likely to have good mental health. Conclusions: These findings confirm the importance of strengthening spirituality as the main protective factor, in addition to the need for interventions to improve peer relationships and social support to optimize the mental health of pesantren-based adolescents.